Evaluasi Penerimaan CPNS bagi Penyandang Disabilitas di Pemerintah Provinsi Kalimantan Selatan - Masrudi Muchtar; Utomo; Latifa Suhada Nisa; Dewi Siska; Maliani (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2020)
The recruitment of civil servant for persons with disabilities by the Provincial Government of South Kalimantan is one of the manifestations of Law No. 8 of 2016 concerning Persons with Disabilities. The law changes the paradigm that makes persons with disabilities as dignified humans who have the same rights as other citizens, including the right to decent work. Affirmation policies have been given to persons with disabilities, but in practice, there are still people with disabilities who feel discriminated against. This condition needs to be evaluated. The purpose of this study is to describe the implementation of civil servant recruitment for persons with disabilities and its compliance with existing policies and also to formulate a policy strategy for the next recruitment. The implementation of civil servant recruitment in 2018 is generally carried out well, except that there are problems with the recruitment of CPNS for persons with disabilities that are not fully in accordance with the policy of respecting, protecting, and fulfilling the rights of persons with disabilities. There are several strategies for implementing civil servant recruitment for persons with disabilities, there are: 1) Conducting equal perceptions between central government, regional government, and other related parties, 2) Building positive concepts for persons with disabilities, 3) Providing greater opportunities for persons with disabilities to become civil servant, 4) Arrange the formation of persons with disabilities based on regional needs and persons with disabilities, 5) Conduct planning of implementation of civil servant recruitment for persons with disabilities by involving the community of persons with disabilities and related parties, 6) Optimizing services for persons with disabilities. Keywords: Evaluation, Civil Servant Recruitment, People with Disabilities ABSTRAK Pelaksanaan penerimaan CPNS bagi penyandang disabilitas oleh Pemerintah Provinsi Kalimantan Selatan merupakan salah satu perwujudan dari Undang-Undang Nomor 8 Tahun 2016 tentang Penyandang Disabilitas. Undang-Undang tersebut merubah paradigma yang menjadikan penyandang disabilitas sebagai manusia yang bermartabat yang memiliki hak yang sama dengan warga negara lainnya, salah satunya hak mendapatkan pekerjaan yang layak. Kebijakan afirmasi telah diberikan kepada penyandang disabilitas, tetapi dalam pelaksanaannya masih ada penyandang disabilitas yang merasakan diskriminasi. Kondisi tersebut melatarbelakangi perlunya evaluasi pelaksanaan penerimaan CPNS bagi penyandang disabilitas. Tujuan dari penelitian ini adalah untuk menggambarkan pelaksanaan penerimaan CPNS bagi penyandang disabilitas dan kesesuaiannya dengan kebijakan yang telah ada, serta merumuskan strategi kebijakan pelaksanaan penerimaan CPNS bagi penyandang disabilitas pada kesempatan berikutnya. Pelaksanaan penerimaan CPNS tahun 2018 pada umumnya terlaksana dengan baik, hanya saja terdapat permasalahan penerimaan CPNS bagi penyandang disabilitas yang belum sepenuhnya sesuai dengan kebijakan penghormatan, perlindungan, dan pemenuhan hak penyandang disabilitas, diantaranya penyandang disabilitas tidak dapat melamar pada formasi umum dan formasi khusus yang disediakan tidak sesuai dengan latar belakang pendidikan yang disediakan untuk penyandang disabilitas. Terdapat beberapa strategi pelaksanaan penerimaan CPNS bagi penyandang disabilitas, diantaranya: 1) Melakukan penyamaan persepsi antar pemerintah pusat, pemerintah daerah dan pihak terkait lainnya, 2) Menyusun formasi penyandang disabilitas berdasarkan kebutuhan daerah dan penyandang disabilitas, 3) Mengoptimalkan pelayanan bagi penyandang disabilitas. Kata Kunci : Evaluasi, Penerimaan CPNS, Penyandang Disabilitas